2016
DOI: 10.17265/1548-6591/2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Sensory Marketing on Consumers: A Case Study of KFC

Abstract: Sensory marketing is a useful marketing application which gives companies a real opportunity to maximize product profitability. Consumers' eating habits keep changing everyday away from their regular meal, less time and more working hours have left people with the option to just pop in a restaurant or fast-food. The use of five senses in the marketing field helps to arouse customer's emotions and nowadays it is fundamental for the company to differentiate itself from its competitors. The study will seek to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
0
9
0
4
Order By: Relevance
“…According to the perspective of Signalling theory, CI is an associations perception that is held by clients in their psyche, as it empowers the clients to see and assess the entire tasks of the association (Kim and Lee, 2010). Moreover, Randhir et al (2016) showed that CI is straightforwardly connected with various authoritative characteristics, for example, brand name, items, administration classification, nature of the item and administrations which are spoken with every client. Moreover, they presumed that CI decidedly affects dependability as they gain proof from various administrations areas such as telecom, training and retailing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the perspective of Signalling theory, CI is an associations perception that is held by clients in their psyche, as it empowers the clients to see and assess the entire tasks of the association (Kim and Lee, 2010). Moreover, Randhir et al (2016) showed that CI is straightforwardly connected with various authoritative characteristics, for example, brand name, items, administration classification, nature of the item and administrations which are spoken with every client. Moreover, they presumed that CI decidedly affects dependability as they gain proof from various administrations areas such as telecom, training and retailing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dani and Pabalkar [3] argue that food and drink tend to be strongly associated with happy or positive memories and that is why the taste aspects of marketing should not be neglected. Randhir et al [7] consider taste marketing to be effective and relatively often used to influence customers through samples and tastings. Customers are more willing to buy a product they have already tried and tasted, rather than one they do not know.…”
Section: Taste and The Taste Marketingmentioning
confidence: 99%
“…In fact, it was the same product, the only difference being the different sounds, which evoked different characteristics in the minds of consumers [22]. Randhir et al [7], in turn, mention the importance of linking flavors and colors, which plays an important role, especially in the product packaging design process. Researchers have found that there is a relationship between taste and color.…”
Section: Taste and The Taste Marketingmentioning
confidence: 99%
See 2 more Smart Citations